Magnetic Nano Fe3O4 Catalyzed Solvent-Free Stereo- and Regioselective Aminolysis of Epoxides by Amines; a Green Method for the Synthesis of β-Amino Alcohols - Kumar, Amit; Parella, Ramarao; Babu, Srinivasarao Arulananda (Synlett, 2014)
We report the use of magnetic nano Fe3O4 as a mild heterogeneous catalyst for the aminolysis of epoxides with amines. The approach constitutes a green method for the formation of a variety of β-amino alcohols with very high stereo- and regioselectivity under solvent-free and ambient reaction conditions. The aminolysis of chiral epoxides with amines gave the corresponding chiral β-amino alcohols with complete inversion of stereochemistry. The magnetic nano Fe3O4 catalyst can be easily recovered and recycled.
Keywords: amino alcohols; epoxides; green chemistry; nano magnetite; regioselectivity; stereoselective synthesis